Obesity - Blades, Mabel (Nutrition & food science ;, 2005)
This e-book focuses on obesity from a number of perspectives and features international articles from the UK, USA, Canada, Australia and Brazil. Obesity is considered by the World Health Organisation to constitute a worldwide epidemic. The release of this e-book coincides with the National Obesity Forum conference held in London, October 2005.